TEACHING THE FUNDAMENTALS OF PEDAGOGICAL COMMUNICATION VILLAGE IN HIGH SCHOOL (Pedagogy of Higher and Secondary Education, 2022)
The article deals with the problem of training in basics of pedagogical communication at USA higher colleges as a factor of professional development of the future specialist by means of training in intensive communication groups, creating laboratories of pedagogical guidance and pedagogical tutorship.